SINKRONISASI KEARIFAN LOKAL TERHADAP PERNIKAHAN (Studi Kasus di Nagari Gunuang Rajo Kecamatan Batipuh) - Muhammad Iqbal; Yustiloviani Yustiloviani (UIN Mahmud Yunus Batusangkar, 2022)
This study examines the rules for having to confess Mamak for marriage by the people of Nagari Gunuang Rajo, Batipuh District for immigrants, the problem is the process of confessing Mamak for couples who are about to get married in Nagari Gunuang Rajo, Batipuh District, is stated in the data on the Nagari Adat Density Rule (KAN) Gunuang Rajo, CHAPTER IV article 3 of 2003 concerning the procedures for higgok mancakam tabang basitumpu or malakok ka Pangulu which reads: paying half gold for KAN administration, paying a quarter of gold for the graceful handed over to the pangalu present at the handover of both parties, paying a quarter of gold for the contents of jujuangan bundo kanduang, from this problem the question arises as to what extent the function of a marriage is for the Gunuang Rajo people, for couples who are about to get married cannot have a wedding in Nagari Gunuang Rajo if they have not confessed that they are Mamak. However, Islamic law does not regulate this. After the data was collected using research methods that were directly carried out in the field and analyzed inductively the results of the research resulted that according to Islamic law it is not an act that prevents people from getting married. However, the purpose of this rule is to regulate that the children of the mMamakwho are in Nagari Gunuang Rajo really understand the customary rules that lead to happiness in marriage so that the implementation of confessing mamak before marriage in Nagari Gunuang Rajo is reviewed by Islamic law, including the category of al- adha sahih or al-urf shahih.